2018
DOI: 10.5539/ijel.v8n6p281
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Intensive English Program on the Vocabulary Size of Lebanese English Foreign Learners

Abstract: The research concerning intensive programs in general has yielded conflicting results and as such, whether or not such time-shortened courses are effective in achieving their learning objectives is a matter of controversy. This study hopes to contribute to the current body of research available and perhaps aid in clearing the uncertainty surrounding such compact programs in a foreign language context by evaluating the effectiveness of one IEP at an English-medium university in Lebanon through the construct of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…In the EFL of Lebanese context, the English Intensive Program effectively improved students' English language proficiency by improving their CEFR level (Abouzeid, 2018). This study highlighted that intensive program could be successful by optimizing prioritized learningfocusing on a task or project in an intensive program.…”
Section: Toefl Preparation Course As English Intensive Programmentioning
confidence: 79%
See 1 more Smart Citation
“…In the EFL of Lebanese context, the English Intensive Program effectively improved students' English language proficiency by improving their CEFR level (Abouzeid, 2018). This study highlighted that intensive program could be successful by optimizing prioritized learningfocusing on a task or project in an intensive program.…”
Section: Toefl Preparation Course As English Intensive Programmentioning
confidence: 79%
“…English intensive program refers to a course in which students participate in a higher number of classes in a shorter period (Mukundan et al, 2012). Some studies showed that this program was a matter of controversy as an effective strategy in achieving students' learning outcomes (Abouzeid, 2018). Kops (2014) found that an English intensive course effectively enhanced students' achievement and reported positive feedback.…”
Section: Toefl Preparation Course As English Intensive Programmentioning
confidence: 99%